Fascisme, historiographie et Résistance: entretien avec Robert O. Paxton / Fascism, Historiography and Resistance: Interview with Robert O. Paxton - Gaspar Celaya, Diego (Historiografías, 2018)
Professor Robert O. Paxton is one of the greatest historians who has most reflected on France, fascism and Europe during World War II. His research has changed the historical understanding of France’s Vichy régime, as he used exceptional empirical evidence to demonstrate that Vichy was a voluntary program, at least at first, more than one forced on France by German pressure. In this interview he is asked about some burning issues concerning fascism historiography today, the Spanish case, and also his personal point of view about the relationship between history and memory about World Word II in France. This gives him cause to review topics such as historiography, present tendencies in fascism studies, the specificities of Franco’s régime and the dominant post war memories in France. Key words Fascism, memory, Resistance, francoism. Abstract Le Professeur Robert O. Paxton est l’un des plus grands historiens qui ait réfléchi sur la France, le fascisme et l’Europe pendant la Seconde Guerre mondiale. Ses recherches ont changé la compréhension de l’histoire du régime de Vichy en France. Il a notamment démontre que Vichy était un programme volontaire, au moins au début, plutôt qu’une contrainte sous la pression allemande. Dans cette interview, il est interrogé à propos de questions brûlantes qui concernent l’historiographie du fascisme aujourd’hui, le développement du fascisme en Espagne, et aussi son point de vue personnel sur la relation entre histoire et mémoire de la seconde Guerre mondiale en France. Cette type de question a permis à monsieur Paxton d’examiner des thèmes tels que les tendances actuelles de l’historiographie sur le fascisme, les spécificités du régime de Franco et les souvenirs et mémoires qui dominent l’après-guerre en France par rapport à la période de Vichy et à la Résistance. Mots clé. Fascisme, mémoire, Résistance, franquisme.